1992
DOI: 10.1079/bjn19920078
|View full text |Cite
|
Sign up to set email alerts
|

Chromium supplementation in impaired glucose tolerance of elderly: effects on blood glucose, plasma insulin, C-peptide and lipid levels

Abstract: - ~~~_Altogether twenty-six elderly subjects (aged 65-74 years) with persistent impaired glucose tolerance (World Health Organization (1985) criteria) identified in a population-based study, were randomly treated either with chromium-rich yeast (160 pg Cr/d) or with placebo for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 24 publications
2
44
1
Order By: Relevance
“…Among the nine studies of participants with glucose intolerance (20,(32)(33)(34)39,46,53,54,58), only Anderson et al (32,33), in two separate studies of 200 g/day chromium chloride, reported statistically significant improvements in postload glucose levels with chromium supplementation: in one, an 8% reduction in 4-h AUC-Glu (but not in 3-h AUCGlu) and in the other a 1.1 mmol/l reduction in 90-min postload glucose. Other studies of all four chromium formulations reported nonsignificant changes in AUC-Glu of Ϫ21 to ϩ3% and in various timed postload glucose levels of Ϫ1.5 to ϩ0.4 mmol/l.…”
Section: Participants With Glucose Intolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Among the nine studies of participants with glucose intolerance (20,(32)(33)(34)39,46,53,54,58), only Anderson et al (32,33), in two separate studies of 200 g/day chromium chloride, reported statistically significant improvements in postload glucose levels with chromium supplementation: in one, an 8% reduction in 4-h AUC-Glu (but not in 3-h AUCGlu) and in the other a 1.1 mmol/l reduction in 90-min postload glucose. Other studies of all four chromium formulations reported nonsignificant changes in AUC-Glu of Ϫ21 to ϩ3% and in various timed postload glucose levels of Ϫ1.5 to ϩ0.4 mmol/l.…”
Section: Participants With Glucose Intolerancementioning
confidence: 99%
“…Anderson et al (44) found a dose effect where high doses of chromium picolinate (1,000 g/day) were more effective than low doses (200 g/day, P Ͻ 0.05), but Kleefstra et al (45) found no difference between 1,000 and 500 g/ day. No study of participants with glucose intolerance found a statistically significant effect of chromium supplementation on glycosylated hemoglobin (20,39,51).…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…44 This will, however, not necessarily mean that the risk factor for impaired glucose tolerance is increased. Uusitupa et al 45 found that although elderly subjects in Finland consumed on averagè 30 mg.day 71 of Cr, this was not found to be an important risk factor for impaired glucose tolerance. Long-term supplementation of 160 mg Cr per day was not effective in normalizing glucose and insulin metabolism.…”
Section: Effectiveness Of Cr-pic On Blood Parametersmentioning
confidence: 99%
“…Many products available on the market contain chromium compounds used as a dietary supplement enhancing the digestion of lipids, and their use is based on studies indicating that chromium together with insulin increase the use of glucose (SHERMAN et al 1968, UUSITUPA et al 1992, AMATO et al 2000, TROW et al 2000, MIZERSKA et al 2005. The process of digestion of lipids starts in the stomach under the effect of sublingual lipase and lipase secreted by the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%